Randomised controlled factorial trial of dietary advice for patients with a single high blood pressure reading in primary care. Issue 7447 (13th April 2004) - Little, Paul; Kelly, Jo; Barnett, Jane; Dorward, Martina; Margetts, Barrie; Warm, Daniel
Abstract: Objective To assess the effect of brief interventions during the "watchful waiting" period for hypertension. Design Factorial trial. Setting General practice. Methods 296 patients with blood pressure > 160/90 mm Hg were randomised to eight groups defined by three factors: an information booklet; low sodium, high potassium salt; prompt sheets for high fruit, vegetable, fibre; and low fat. Main outcome measures Blood pressure (primary outcome); secondary outcomes of diet, weight, and dietary biomarkers (urinary sodium:potassium (Na:K) ratio; carotenoid concentrations). Results Blood pressure was not affected by the booklet (mean difference (diastolic blood pressure) at one month 0.2, 95% confidence interval 1.6 to 2.0), salt (0.13; 1.7 to 2.0), or prompts (0.52; 1.3 to 2.4). The salt decreased Na:K ratio (difference 0.32; 0.08 to 0.56, P = 0.01), and the prompts helped control weight (difference 0.39 (0.85 to 0.05) kg at one month, P = 0.085; 1.2 (0.1 to 2.25) kg at six months, P = 0.03). Among those with lower fruit and vegetable consumption (< 300 g per day), prompts increased fruit and vegetable consumption and also carotenoid concentrations (difference 143 (16 to 269) mmol/l, P < 0.03) but did not decrease blood pressure. Conclusion During watchful waiting, over and above the effect of brief advice and monitoring, an information booklet, lifestyle prompts, and low sodium salt do not reduce blood pressure. Secondary analysis suggests that brief interventions—particularly lifestyle prompts—can make useful changes in diet and help control weight, which previous research indicates are likely to reduce the long term risk of stroke.